Outcome Mapping and innovation platforms in the imGoats project: Reflections from Mozambique - Maheme, A.A. (International Livestock Research Institute, 2013)
The imGoats project (imgoats.org) seeks to investigate how best goat value chains can be used to increase food security and reduce poverty among smallholders in India and Mozambique. Funded by the International Fund for Agricultural Research (IFAD), the project is led by researchers from the International Livestock Research Institute (ILRI) in collaboration with the BAIF Development Research Foundation in India and CARE International in Mozambique. On 2-6 July 2012, the imGoats project held a learning and reflection workshop in Udaipur, India. The purpose of the workshop was to take stock of the key areas of work, challenges and opportunities; reflect on the use of Outcome Mapping and innovation platforms; and plan for communications activities for the remaining six months of the project. On the sidelines of the workshop, Amosse Alberto Maheme, imGoats project officer at CARE Mozambique, shared some of his reflections on the workshop activities, his experiences with applying the theory of Outcome Mapping in the field, and his outlook for the final six months of the project and the sustainability of the activities already implemented. Originally released 21 July 2012.